Introduction to polymer compounding. Volume 1 - Muralisrinivasan, Natamai Subramanian (Smithers Rapra, 2014)
Polymer Compounding, Volume 1 focuses on aspects of the raw materials used in polymer processing. Polymer compounding comprises a complex heterogeneous system of polymers and other ingredients and, in many ways, the preparation of these materials is still very much an art. It is a powerful tool that will eventually be required as one of the basics of polymer processing. . This book provides readers with a wide array of state-of-the-art strategies to develop their knowledge about compounding and the use of polymers while minimising wastage during processing. Details about polymer properties and.
"A Smithers Group Company"--T.p.
Keywords: Polymers.; Thermoplastics.; elektronické knihy; electronic books